Enhancing cellular immune response to HBV M DNA vaccine in mice by codelivery of interleukin-18 recombinant - 陈建忠 朱海红 刘克洲 陈智 (Journal of Zhejiang University. A. Science, 2004)
Objective:To investigate the effect of interleukin-18 (IL-18) on immune response induced by plasmid encoding hepatitis B virus middle protein antigen and to explore new strategies for prophylactic and therapeutic HBV DNA vaccines.Methods:BALB/c mice were immunized with pCMV-M alone or co-immunized with pcDNA3-18 and pCMV-M and then their sera were collected for analysing anti-HBsAg antibody by ELISA;splenocytes were isolated for detecting specific CTL response and cytokine assay in vitro.Results:The anti-HBs antibody level of mice co-immunized with pcDNA3-18 and pCMV-M was slightly higher than that of mice immunized with pCMV-M alone,but there was not significantly different (P>0.05).Compared with mice injected with pCMV-M, the specific CTL cytotoxity activity of mice immunized with pcDNA3-18 and pCMV-M was significantly enhanced (P<0.05) and the level of IFN-γ in supernatant of splenocytes cultured with HBsAg in vitro was significantly elevated (P<0.05) while the level of IL-4 had no significant difference (P>0.05).Conclusion:The plasmid encoding IL-18 together with HBV M gene DNA vaccines may enhance specific TH1 cells and CTL cellular immune response induced in mice, so that IL-18 is a promising immune adjuvant.